Nerve growth factor mediates a switch in intracellular signaling for PGE2-induced sensitization of sensory neurons from protein kinase A to Epac. - Michael R Vasko (Public Library of Science (PLoS), 2014)
We examined whether nerve growth factor (NGF), an inflammatory mediator that contributes to chronic hypersensitivity, alters the intracellular signaling that mediates the sensitizing actions of PGE2 from activation of protein kinase A (PKA) to exchange proteins directly activated by cAMP (Epacs). When isolated sensory neurons are grown in the absence of added NGF, but not in cultures grown with 30 ng/ml NGF, inhibiting protein kinase A (PKA) activity blocks the ability of PGE2 to augment capsaicin-evoked release of the neuropeptide CGRP and to increase the number of action potentials (APs) evoked by a ramp of current. Growing sensory neurons in culture in the presence of increasing concentrations of NGF increases the expression of Epac2, but not Epac1. An intradermal injection of complete Freund's adjuvant into the rat hindpaw also increases the expression of Epac2, but not Epac1 in the dorsal root ganglia and spinal cord: an effect blocked by intraplantar administration of NGF antibodies. Treating cultures grown in the presence of 30 ng/ml NGF with Epac1siRNA significantly reduced the expression of Epac1, but not Epac2, and did not block the ability of PGE2 to augment capsaicin-evoked release of CGRP from sensory neurons. Exposing neuronal cultures grown in NGF to Epac2siRNAreduced the expression of Epac2, but not Epac1 and prevented the PGE2-induced augmentation of capsaicin and potassium-evoked CGRP release in sensory neurons and the PGE2-induced increase in the number of APs generated by a ramp of current. In neurons grown with no added NGF, Epac siRNAs did not attenuate PGE2-induced sensitization. These results demonstrate that NGF, through increasing Epac2 expression, alters the signaling cascade that mediates PGE2-induced sensitization of sensory neurons, thus providing a novel mechanism for maintaining PGE2-induced hypersensitivity during inflammation.